AGE-RELATED DIFFERENCES IN ANTIMICROBIAL RESISTANCE AND MRSA IN URINARY TRACT INFECTIONS: EVIDENCE FROM BALOCHISTAN (Journal of Medical & Health Sciences Review, 2025)
Urinary tract infections (UTIs) remain one of the most common bacterial infections worldwide, with antimicrobial resistance (AMR) posing a growing challenge to effective treatment. This study investigates age-related variations in antimicrobial resistance patterns, with a particular focus on methicillin-resistant Staphylococcus aureus (MRSA), among patients presenting with UTIs in Balochistan. Clinical samples were collected from diverse age groups and analyzed using standard microbiological techniques to identify causative organisms and their resistance profiles. The findings revealed significant differences in resistance rates across age categories, with elderly patients showing higher prevalence of multidrug-resistant strains, including MRSA, compared to younger cohorts. Resistance to commonly prescribed antibiotics such as fluoroquinolones and cephalosporins was widespread, underscoring the diminishing efficacy of first-line therapies. The study highlights the urgent need for age-specific surveillance strategies and tailored treatment guidelines to address the growing burden of AMR in UTIs. These results provide critical evidence for public health authorities in Balochistan to strengthen antimicrobial stewardship programs and improve clinical outcomes across all age groups.